The hidden footprint of Engagement: discovering its effects on Workplace Stress and Hiding Feelings - Papanestoras, Christos; Guinot Reinders, Jacob; Chiva Gómez, Ricardo (Cuadernos de Administración, 2024)
n this paper we examine the relationships between employee engagement, stress and concealment of feelings in the workplace. This exploration sheds light on the intricate dynamics at play, providing a comprehensive understanding of these elements and their interactions. By exploring these relationships, we contribute to a more accurate understanding of the impact of engagement on employee well-being. While most of the evidence focuses on uncovering the positive effects of engagement at work, some evidence and research also suggests that engagement may have a dark side on well-being at work. To explore these relationships, our research employs Structural Equation Modelling (SEM) on data from the 2015 European Working Conditions Survey (EWCS) conducted by Eurofound, using a consistent sample of 1,007 employees in Greece. Although a significant negative effect is observed between engagement and stress, as suggested by mainstream and previous research, the model finds positive associations between engagement and hiding feelings, and between hiding feelings and stress. Additionally, the results highlight variations based on control variables such as sector and gender, indicating that the impact of engagement on stress and concealment of emotions can differ across different work environments and between genders. These findings allow for a better understanding of the potential effects of engagement, helping to re-evaluate human resource management interventions and opening up alternative avenues in well-being research.